Two Rab5 Homologs Are Essential for the Development and Pathogenicity of the Rice Blast Fungus Magnaporthe oryzae - Yang, Cheng D.; Dang, Xie; Zheng, Hua W.; Chen, Xiao F.; Lin, Xiao L.; Zhang, Dong M.; Abubakar, Yakubu S.; Chen, Xin; Lu, Guodong; Wang, Zonghua; Li, Guangpu; Zhou, Jie (Frontiers in Plant Science, 2017)
The rice blast fungus, Magnaporthe oryzae, infects many economically important cereal crops, particularly rice. It has emerged as an important model organism for studying the growth, development and pathogenesis of filamentous fungi. Rab GTPases are important molecular switches in regulation of intracellular membrane trafficking in all eukaryotes. MoRab5A and MoRab5B are Rab5 homologs in M. oryzae, but their functions in the fungal development and pathogenicity are unknown. In this study, we have employed a genetic approach and demonstrated that both MoRab5A and MoRab5B are crucial for vegetative growth and development, conidiogenesis, melanin synthesis, vacuole fusion, endocytosis, sexual reproduction and plant pathogenesis in M. oryzae. Moreover, both MoRab5A and MoRab5B show similar localization in hyphae and conidia. To further investigate possible functional redundancy between MoRab5A and MoRab5B, we overexpressed MoRAB5A and MoRAB5B, respectively, in MoRab5BRNAi and MoRab5ARNAi mutants, but neither could rescue each other’s defects caused by the RNAi. Taken together, we conclude that both MoRab5A and MoRab5B are necessary for the development and pathogenesis of the rice blast fungus, while they may function independently.